2017
DOI: 10.1007/s00127-017-1449-y
|View full text |Cite
|
Sign up to set email alerts
|

Short video interventions to reduce mental health stigma: a multi-centre randomised controlled trial in nursing high schools

Abstract: Seminar had the strongest and relatively stable effect on students' attitudes and intended behaviour, but the effect of short video interventions was also considerable and stable over time. Since short effective video interventions are relatively cheap, conveniently accessible and easy to disseminate globally, we recommend them for further research and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 43 publications
3
43
1
1
Order By: Relevance
“…The two other studies had duration of one [ 24 ] and eight weeks [ 32 ]. Winkle et al (2017) reported small effect size for flyer or control group and medium effect size for the experimental group [ 22 ]. After a psychiatry clerkship, medical students reported improvement in stigmatizing attitudes but there was no improvement in attributions regarding responsibility and readiness to provide care to patients with mental illnesses [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The two other studies had duration of one [ 24 ] and eight weeks [ 32 ]. Winkle et al (2017) reported small effect size for flyer or control group and medium effect size for the experimental group [ 22 ]. After a psychiatry clerkship, medical students reported improvement in stigmatizing attitudes but there was no improvement in attributions regarding responsibility and readiness to provide care to patients with mental illnesses [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies [41] [42] [47]- [55] were reviewed carefully and included in this review. In Table 1, each included study in this review was summarized and described in terms of: authors, year of publication, aim, intervention, and main results.…”
Section: Resultsmentioning
confidence: 99%
“…Winkler, Janoušková, Kožený, Pasz, Mladá, Weissová, Tušková, and Evans-Lacko (2017) [42]; both social contact and video-based social contact.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations